Nephroprotective Activities of Ethanol Root Extract and Fractions of Hippocratea africana Against Doxorubicin-Induced Kidney Toxicity - Noah, Kufre U.; Udobang, John A.; Okokon, Jude E.; Anagboso, Martin O.; Ebong, Nwakaego Omonigho (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Hippocratea africana root used locally in the treatment of poisoning was investigated to confirm its antidotal potential in rats. The root extract (200-600 mg/kg) and fractions; dichloromethane (DCM) and aqueous, 400 mg/kg) were evaluated for nephroprotective activity against doxorubicin-induced kidney injury in rats. Kidney function parameters, kidney oxidative stress markers and kidney histology were used to assess the kidney protective effect of the extract. The root extract and fractions (200-600 mg/kg) significantly (p<0.05-0.01) reduced the levels of creatinine, urea and electrolytes that were elevated by doxorubicin. Also, the MDA level elevated by doxorubicin was reduced by the extract and fractions co-administration, while the levels of GSH, GST, SOD, GPx, and CAT that were decreased by doxorubicin were significantly (p<0.01) elevated by the root extract/fractions. Histology of the kidney sections of extract/fractions -treated animals showed reductions in the pathological features compared to the organotoxic-treated animals. The chemical pathological changes were consistent with histopathological observations suggesting marked nephroprotective potential. The anti-toxic effect of this plant may in part be mediated through the chemical constituents of the plant. The plant, Hippocratea africana possesses anti-toxicant properties which can be exploited in the treatment of doxorubicin related toxicities.